Is Transformational Leadership Healthy for Employees? A Multilevel Analysis in 16 Nations. (February 2014) - Zwingmann, Ina; Wegge, Jürgen; Wolf, Sandra; Rudolf, Matthias; Schmidt, Matthias; Richter, Peter
This study examines the potential health promoting and hampering effects of transformational, contingent reward and laissez-faire leadership across 16 countries with a multi-source dataset comprising 93, 576 subordinates in 11, 177 teams of a large international company. We analyze how leadership climate strength, defined as the shared perceptions of employees concerning their supervisor's leadership behavior, affects individual employees' health and if leaders who are both transformational and transactional have more healthy employees (augmentation effect). In addition, we investigate how national power distance moderates these relationships. The results of multi-level analysis provide strong support for the health promoting effect of transformational leadership ( r = .16 to r = .50), contingent reward ( r = .14 to r = .48) and the health hampering effect of laissez-faire leadership ( r = -.15 to r = -.43) within the analyzed 16 nations. Having a strong transformational leadership climate is also associated with better perceived health in eight countries. Finally, the augmentation effect was significant in six countries and we also found, as expected, that a high power distance strengthens the health promoting effects of transformational leadership. Overall, this study indicates that having a shared vision as well as clear goals, roles and rewards at work is important for promoting employees' health worldwide.